Controlling charge and spin delocalization in porphyrin nanomaterials – synthesis and magnetic resonance studies - Kopp, SM (2024)
The research presented in this thesis describes the synthesis and spectroscopic investigation of porphyrin nanomaterials with tailored electronic and magnetic properties. A detailed understanding of the factors that govern the distribution of charge and spin carriers in π-conjugated molecules is important for the rational design of new materials with potential applications in molecular electronic, spintronic, and photonic devices. Electron paramagnetic resonance (EPR) spectroscopy, steady-state and transient optical absorption spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, and quantum chemical calculations were employed throughout this thesis to study charge and spin delocalization.